ANTIOXIDATIVE AND FREE RADICAL SCAVENGING ACTIVITY OF ETHANOLIC EXTRACT OF LENTINULA EDODES - Devi, L. Sushila; Ghosh, Shouvik; Das, Arpita; Borthakur, S.K.; Singh, N. Irabanta (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Aim of this work was to evaluate the antioxidant properties of the edible mushroom species, Lentinula edodes. Methods: Presence of potential antioxidant compounds, such as, ascorbic acid, Î² carotene, lycopene, phenolics and flavonoids were tested. To understand the antioxidant potentiality like scavenging of superoxide radical, chelating of ferrous ion, scavenging capacity of DPPH radicals and reducing power of the extract were investigated. Results: The extraction yield achieved from L. edodes extraction was 2.4%. Total phenolic content was 25.5 mg GAE/g and total flavonoids content was 2 mg CE/g. The EC50 value for superoxide radical scavenging activity was found to be at a concentration of 0.64 mg/ml. Conclusion: The results obtained reveal that L. edodes can be a potential source of natural antioxidant which may be used to treat various oxidative stress related diseases. Key words: Ascorbic acid, edible mushroom, Lentinula edodes, flavonoids, phenols, reactive oxygen species